United States Law’s Failure to Appreciate Art: How Public Art Has Been Left Out in the Cold - Emma G. Stewart (Washington University Law Review, 2020)
The Visual Artists Rights Act (VARA) does not sufficiently protect public artists’ moral rights. A better understanding of public art from an artistic, rather than legal, point of view can help lawmakers and courts identify and implement more sufficient protections. An artistic perspective is necessary when considering VARA reform because it encourages a deeper appreciation of the value of many forms of artistic expression. The broader and more flexible definition of visual art proposed by this Note can help bridge the gap between art and art law by offering legal protection to a wider breadth of works that are invariably recognized as art by art scholars and consumers, but not by legal scholars and judges. These changes cannot and should not occur overnight, and thus the first step to the preservation of America’s public artworks is a more widespread recognition of the important role that public art, and therefore the artists who create it, plays in our everyday lives.
Keywords: Visual artists rights act; Public art; Legal protection for art; Visual art; Art appreciation